Making Connections: Reading Barbara Kingsolver’s Works from an Ecofeminist Partnership Ethics Perspective - Abhra Paul; Vidya Sarveswaran (European Journal of American Studies)
The ecofeminist epistemologies recognize the ecological and social interdependencies in the planetary system. Carolyn Merchant’s (2014) concept of partnership ethics is grounded on the interdependencies between the biotic and abiotic communities: “A partnership ethic holds that the greatest good for the human and nonhuman communities is in their mutual living interdependence” (83). Following this line of thought, this paper studies Barbara Kingsolver’s fiction and nonfiction, namely, High Tide in Tucson (1995), Small Wonder (2003), Prodigal Summer (2000), Flight Behaviour (2012), and Animal Dreams (1990) through the lens of Ecofeminist Partnership Ethics (Carolyn Merchant 2014) and foregrounds the interrelationship between women, women-nature, and human-nature. This paper also analyses the ecofeminist thoughts of Karren Warren, Val Plumwood, and Carolyn Merchant and how Kingsolver’s works repudiate the limitations of dualistic thinking (culture/nature, man/woman) and the subordination of nature and women.